2022
DOI: 10.1111/acer.14843
|View full text |Cite
|
Sign up to set email alerts
|

What is the optimum thiamine dose to treat or prevent Wernicke's encephalopathy or Wernicke–Korsakoff syndrome? Results of a randomized controlled trial

Abstract: Background:The primary cause of Wernicke-Korsakoff syndrome (WKS) is thiamine deficiency, and more than 90% of cases are reported in alcohol-dependent patients.While observational studies show parenteral thiamine administration drastically reduced WKS-related mortality, relevant treatment trials have never been conducted to determine the optimum thiamine dose.Methods: Two double-blind, parallel groups, randomized controlled trials (RCTs) were conducted to determine the optimal thiamine dose required for (1) th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…(2001) in which AUD patients received a daily dosage of either 5, 20, 50, 100, or 200 mg of intramuscular thiamine, a dose depending effect of thiamine on cognitive functioning, specifically on working memory, was reported. However, this finding could not be replicated in a consecutively conducted study ( Dingwall et al. 2022 ) by the same research group.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…(2001) in which AUD patients received a daily dosage of either 5, 20, 50, 100, or 200 mg of intramuscular thiamine, a dose depending effect of thiamine on cognitive functioning, specifically on working memory, was reported. However, this finding could not be replicated in a consecutively conducted study ( Dingwall et al. 2022 ) by the same research group.…”
Section: Discussionmentioning
confidence: 75%
“…utilization of thiamine esters in patients with alcohol-related liver disease, the presence of additional nutritional deficiencies such as magnesium deficiency) potentially interfering with thiamine metabolism complicates research efforts concerning this matter ( Martin et al. 2003 ; Dingwall et al. 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Imaging of the head and cerebral spinal fluid studies may be required (144). It is also important to rule out Wernicke encephalopathy as a cause for altered mental status because it has its own prognostic and management implications (145,146), especially when considering LT for patients with ALD.…”
Section: Hepatic Encephalopathymentioning
confidence: 99%
“…3 There is no consensus on the optimal dose and duration of parenteral thiamine, but its short half-life and water solubility suggest that divided dosing (2 or 3 times daily) would lead to better tissue repletion than once-daily dosing. [3][4][5][6]…”
Section: Qmentioning
confidence: 99%
“…3,4,5,7 A recent single-center randomized controlled trial comparing different dosages of parenteral thiamine found no evidence of an effect of dose on neurologic and cognitive outcomes in patients at risk for Wernicke encephalopathy; however, this study was limited by small sample size, high attrition, and short duration of follow-up. 6 Fortunately, adverse effects from parenteral thiamine administration are uncommon. Although early case reports of anaphylaxis from rapid administration of intravenous thiamine have raised concern, the risk is now believed to be exceedingly rare, especially when thiamine is administered over 30 minutes.…”
Section: ■ Thiamine Treatment: Route Dosing and Durationmentioning
confidence: 99%